2013
DOI: 10.1128/genomea.00085-12
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Bacteriophage EC6, Capable of Lysing Escherichia coli O157:H7

Abstract: A bacteriophage, EC6, capable of lysing Escherichia coli serotype O157:H7 was isolated and found to be a member of the family Myoviridae. The genomic sequence of phage EC6 was composed of 86,231 bp with a G+C content of 38.9% and is very similar to the sequences of Escherichia phage wV8 and Salmonella phage Felix O1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
(8 reference statements)
0
6
0
Order By: Relevance
“…Both SUSP1 and SUSP2 are members of the family Myoviridae and form clear plaques (see Fig. S6); possess genomes of 90.8 and 88.7 kb, respectively; and are most closely related to Escherichia phage EC6 (21), Citrobacter phage Moogle (22), and other Felix O1-like viruses (see Table S1). Because both SUSP1 and SUSP2 share <90% whole-genome homology with all other published phage sequences and encode a substantial number of hypothetical proteins with unknown biological functions, we considered the possibility that these phages actively produce some type of DNA-protecting factor(s) during infection.…”
Section: Resultsmentioning
confidence: 99%
“…Both SUSP1 and SUSP2 are members of the family Myoviridae and form clear plaques (see Fig. S6); possess genomes of 90.8 and 88.7 kb, respectively; and are most closely related to Escherichia phage EC6 (21), Citrobacter phage Moogle (22), and other Felix O1-like viruses (see Table S1). Because both SUSP1 and SUSP2 share <90% whole-genome homology with all other published phage sequences and encode a substantial number of hypothetical proteins with unknown biological functions, we considered the possibility that these phages actively produce some type of DNA-protecting factor(s) during infection.…”
Section: Resultsmentioning
confidence: 99%
“…strain CcI3) to 9.04 Mbp for a broad host range Elaeagnus strain (EAN1pec) [ 23 ]. In recent years, several more Frankia strains have been sequenced [ 24 31 ]. Analysis of these genomes confirmed that the Frankia genome size correlates positively to host specificity and biogeography ranges [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of these genomes confirmed that the Frankia genome size correlates positively to host specificity and biogeography ranges [ 22 , 23 ]. Presently, genome sequences are available for all four Frankia lineages: Cluster 1 “medium and narrow host range” strains CcI3, ACN14a, CcI6, BMG5.23, Thr, and QA3 [ 23 , 26 , 29 31 ]; Cluster 2 “uncultured” Frankia datiscae Dg1 [ 25 ]; Cluster 3 “broad host range” strains EAN1pec, EUN1f, BMG5.12 and BCU110501 [ 23 , 24 , 27 ]; and Cluster 4 “atypical” strains EuI1c, CN3 and DC12 [ 22 , 24 ]. Atypical Frankia strains used in this study are unable to fix nitrogen, and two (strains CN3 and DC12) are unable to re-infect their host plant.…”
Section: Introductionmentioning
confidence: 99%
“…Since many of the genomes of Felix01-related phages have already been examined in detail and published, herein is provided only a brief overview of VpaE1 genome. Bacteriophage VpaE1 has a linear ds DNA genome of 88,403 bp that is similar in size to those of other Felix01-related viruses whose genome sizes range between 84 and 93 kb [ 19 , 23 , 24 , 27 , 29 , 32 , 33 , 35 ]. As is the case with other virulent phages, the VpaE1 genome has an average mol% G+C content of 38.9%, which differs significantly from that of the host (~50%).…”
Section: Resultsmentioning
confidence: 99%
“…Felix01 has long been considered as a singleton within the family Myoviridae [ 22 ]. However, during the last few years, a dozen of its close relatives, active mainly against E. coli [ 23 , 24 , 25 , 26 , 27 ] or Salmonella [ 28 , 29 , 30 , 31 , 32 ] have been isolated and sequenced. In addition, more distant Felix01 relatives that infect Erwinia [ 33 ], Citrobacter [ 34 ] or Pseudomonas [ 35 ] have been described.…”
Section: Introductionmentioning
confidence: 99%